The Fetish Revisited: Marx, Freud and the Gods Black People Make by J. Lorand Matory. Issue 6 (2nd November 2021) - Haiven, Max
ABSTRACT: J. Lorand Matory demonstrates that the very idea of the fetish stems from a self-aggrandizing European discourse through which the diverse material practices of non-European civilizations were cast down as childish and primitive. Matory directs the anthropological gaze back on Europeans who made a fetish (an object endowed by the human imagination with supernatural power) of the very idea of the fetish. Beyond simply a critique, his text is also a singularly insightful, thoughtful and provocative engagement with the present-day practitioners of traditional West African religions whose ancestors' practices were so fatefully misrecognized as mere 'fetishism' by Europeans. Matory's bold revisitation of the fetish will be important for moving the cultural study of economics and the economic study of culture beyond Eurocentric presumptions and teleologies. Though it is not Matory's stated objective, The Fetish Revisited demands that we fundamentally reevaluate the origin of the tools we use to understand the relationship between culture and economics, between the making of meaning and the creation and exchange of things. Neither solely a critique of Eurocentric thought nor a redemption of Afrocentric thought, it is a call to continue to rethink the economic subject.